ChemInform Abstract: Highly Functionalized and Potent Antiviral Cyclopentane Derivatives Formed by a Tandem Process Consisting of Organometallic, Transition‐Metal‐Catalyzed, and Radical Reaction Steps. Issue 8 (February 2015) - Jagtap, Pratap R.; Ford, Leigh; Deister, Elmar; Pohl, Radek; Cisarova, Ivana; Hodek, Jan; Weber, Jan; Mackman, Richard; Bahador, Gina; Jahn, Ullrich
Abstract An one‐pot reaction sequence is used for the preparation of tetrasubstituted cyclopentanes (V)/(VI).